TEACHING SPEAKING THROUGH ROLE PLAY TO PANDAWA BEACH STAFF AT KUTUH VILLAGE - Ni Made Wersi Murtini; Putu Santhi Widiastuti (Journal on Studies in English Language Teaching (JOSELT), 2020)
This is a classroom action research which aimed to improve the speaking ability of the Pandawa Staff at Kutuh Village. The subjects of this research are 16 people which had low ability at speaking English especially in explaining about Pandawa Beach and its surrounding. It can be seen from the pre test which was 49.81. To solve this problem, the researcher used a speaking technique which is called Role Play to improve their speaking ability. The data of this research were collected from the pre test, post test 1, post test 2, post test 3 which were analyzed with statistical analysis. The result of this researh showed a significant improvement in speaking ability after the implementation Role Play. It can be seen from the average value of the pre cycle, cycle I, cycle II, cycle III, which were: 49.81 ; 59.56; 67.69; and 76.88.